THE INFLUENCE OF MARKETING INNOVATION ADOPTION ON MSME MARKETING PERFORMANCE MEDIATED BY DIGITAL MARKETING: A CASE STUDY AT RUMAH BUMN DENPASAR - I Kade Tirtha Yoga Dwyanthara; Komang Agus Rudi Indra Laksmana; I Dewa Nyoman Usadha; I Ketut Merta (Academic Journal Research, 2026)
Objective: This study investigates the influence of Corporate Social Responsibility (CSR) marketing adoption innovations—comprising Digital Marketing Training Innovation, Marketing Mentoring Innovation, and SME Brand Awareness—on the Online Sales Performance of Micro, Small, and Medium Enterprises (MSMEs) at Rumah BUMN Denpasar, with Digital Marketing serving as a mediating variable. Despite the availability of empowerment programs by PLN UID Bali, data indicate that a significant digital competency gap remains among local MSMEs. Method: Employing a quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM), this research analyzed data from 446 MSMEs. Results: The findings demonstrate that both training and mentoring innovations significantly enhance Digital Marketing adoption. Furthermore, Brand Awareness emerges as a critical determinant for digital platform engagement. Crucially, Digital Marketing significantly boosts Online Sales Performance and proves to be an effective mediator, bridging the impact of CSR innovations on business outcomes. Novelty: These results confirm that CSR initiatives successfully improve digital literacy and foster sustainable marketing capabilities, offering vital insights for strategic MSME development and government policy in the digital era.